DTNQ-Pro, a Mimetic Dipeptide, Sensitizes Human Colon Cancer Cells to 5-Fluorouracil Treatment - Gomez-Monterrey, Isabel (Hindawi Publishing Corporation, 2013)
The resistance of growing human colon cancer cells to chemotherapy agents has been correlated to endogenous overexpression of stress proteins including the family of heat shock proteins (HSPs). Previously, we have demonstrated that a quinone-based mimetic dipeptide, named DTNQ-Pro, induced differentiation of growing Caco-2 cells through inhibition of HSP70 and HSP90. In addition, our product induced a HSP27 and vimentin intracellular redistribution. In the present study, we have evaluated whether a decrease of stress proteins induced by DTNQ-Pro in Caco-2 cells could sensitize these cells to treatment with 5-fluorouracil (5-FU) cytotoxicity. The pretreatment of Caco-2 with 500 nM of DTNQ-Pro increases lipid peroxidation and decreases expression of p38 mitogen-activated protein kinase (MAPK) and FOXO3a. At the same experimental conditions, an increase of the 5-FU-induced growth inhibition of Caco-2 cells was recorded. These effects could be due to enhanced DTNQ-Pro-induced membrane lipid peroxidation that, in turn, causes the sensitization of cancer cells to the cytotoxicity mediated by 5-FU.